Inhibition of platelet activation suppresses reactive enteric glia and mitigates intestinal barrier dysfunction during sepsis - Bo Cheng; Mengyu Du; Shuxuan He; Lan Yang; Xi Wang; Hui Gao; Haiqing Chang; Wei Gao; Yan Li; Qiang Wang; Yansong Li (BMC, 2022)
Abstract Background Intestinal barrier dysfunction, which is associated with reactive enteric glia cells (EGCs), is not only a result of early sepsis but also a cause of multiple organ dysfunction syndrome. Inhibition of platelet activation has been proposed as a potential treatment for septic patients because of its efficacy in ameliorating the organ damage and barrier dysfunction. During platelet activation, CD40L is translocated from α granules to the platelet surface, serving as a biomarker of platelet activation a reliable predictor of sepsis prognosis. Given that more than 95% of the circulating CD40L originate from activated platelets, the present study aimed to investigate if inhibiting platelet activation mitigates intestinal barrier dysfunction is associated with suppressing reactive EGCs and its underlying mechanism. Methods Cecal ligation and puncture (CLP) was performed to establish the sepsis model. 24 h after CLP, the proportion of activated platelets, the level of sCD40L, the expression of tight-junction proteins, the intestinal barrier function and histological damage of septic mice were analyzed. In vitro, primary cultured EGCs were stimulated by CD40L and LPS for 24 h and EGCs-conditioned medium were collected for Caco-2 cells treatment. The expression of tight-junction proteins and transepithelial electrical resistance of Caco-2 cell were evaluated. Results In vivo, inhibiting platelet activation with cilostazol mitigated the intestinal barrier dysfunction, increased the expression of ZO-1 and occludin and improved the survival rate of septic mice. The efficacy was associated with reduced CD40L+ platelets proportion, decreased sCD40L concentration, and suppressed the activation of EGCs. Comparable results were observed upon treatment with compound 6877002, a blocker of CD40L-CD40-TRAF6 signaling pathway. Also, S-nitrosoglutathione supplement reduced intestinal damage both in vivo and in vitro. In addition, CD40L increased release of TNF-α and IL-1β while suppressed the release of S-nitrosoglutathione from EGCs. These EGCs-conditioned medium reduced the expression of ZO-1 and occludin on Caco-2 cells and their transepithelial electrical resistance, which could be reversed by CD40-siRNA and TRAF6-siRNA transfection on EGCs. Conclusions The inhibition of platelet activation is related to the suppression of CD40L-CD40-TRAF6 signaling pathway and the reduction of EGCs activation, which promotes intestinal barrier function and survival in sepsis mice. These results might provide a potential therapeutic strategy and a promising target for sepsis.